THE EFFECTIVENESS OF BIOFEEDBACK IN THE TREATMENT OF DIFFICULT-TO-CONTROL ARTERIAL HYPERTENSION - Tymoshenko, O. S. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
Review is devoted to difficult-to-control arterial hypertension and possibilities of biofeedback as additional method to standard antihypertensive therapy. Reasons and current approaches to therapy of difficult-to-control arterial hypertension are discussed. Particularities of biofeedback therapy and variants of the technical implementation of the different loops are described. Recent publications that contain data of the effectiveness of biofeedback among hypertensive patients are given. Relevance of this problem among patients with difficult-to-control arterial hypertension is proved.